Light-emitting diodes based on colloidal silicon quantum dots. (June 2018) - Zhao, Shuangyi; Liu, Xiangkai; Pi, Xiaodong; Yang, Deren
Abstract: Colloidal silicon quantum dots (Si QDs) hold great promise for the development of printed Si electronics. Given their novel electronic and optical properties, colloidal Si QDs have been intensively investigated for optoelectronic applications. Among all kinds of optoelectronic devices based on colloidal Si QDs, QD light-emitting diodes (LEDs) play an important role. It is encouraging that the performance of LEDs based on colloidal Si QDs has been significantly increasing in the past decade. In this review, we discuss the effects of the QD size, QD surface and device structure on the performance of colloidal Si-QD LEDs. The outlook on the further optimization of the device performance is presented at the end.